A cross-sectional study on health-related knowledge and its predictors among Chinese vocational college students. Issue 10 (13th October 2014) - Wang, Weina; Hou, Yanli; Hu, Nan; Zhang, Dongxian; Tao, Junliang; Man, Yonghong; Wang, Aimei; Li, Ling; Bi, Yongyi
Abstract : Objectives: This study sought to examine the level of health-related knowledge and its predictors among vocational college students in China. Study design: A cross-sectional study. Methods: A survey was performed to collect data on heath-related knowledge and potential risk factors among 708 students in four higher vocational colleges at Nanyang, Henan, China. Linear regression models were conducted to identify the predictors of the level of health-related knowledge. Results: The level of health-related knowledge among Chinese vocational college students is extremely low (only 1.4% students have an adequate level of health-related knowledge). According to the multivariate analysis, major, year of class, place of origin and a mother's education level are significantly associated with health-related knowledge in Chinese vocational college students. Conclusions: Health education and health promotion efforts are encouraged to improve the level of health-related knowledge in this population. Attention and efforts to improve health-related knowledge of Chinese vocational college students who come from rural areas, whose mothers have a lower level of education, who are in non-medicine majors and during the first few years of vocational college is warranted.